Modernisasi Islam di Indonesia Perspektif Nurcholis Madjid Dalam Mengatasi Tantangan Kontemporer - Maksum, Muh. Nur Rochim; Wiratama, Hanif Syairafi (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
This study examines the concept of Islamic modernization through the perspective of Nurcholish Madjid and its role in addressing contemporary challenges. The primary objective is to explore Nurcholish Madjid’s conceptualization of Islamic modernization, focusing on his call for reform that involves a critical departure from traditional values and the adoption of future-oriented principles. To achieve this, a library research method was employed, analyzing both primary texts by Nurcholish Madjid and secondary sources that discuss his contributions to Islamic thought. The findings reveal that, according to Nurcholish Madjid, modernization in Islam requires a dual approach: breaking away from entrenched traditional values that no longer serve as effective benchmarks, and embracing innovative values that address the dynamic realities of the modern era. This research underscores the relevance of his thought in inspiring a renewed understanding of Islam that is capable of responding to current social and cultural challenges. The study concludes that Nurcholish Madjid’s ideas offer a viable framework for reinterpreting Islamic teachings in a way that both preserves the core essence of the faith and promotes progress in the contemporary world